Molecular characterization of Sarcocystis spp. in intestine mucosal scrapings and fecal samples of Pampas fox (Lycalopex gymnocercus) - Scioscia, Nathalia Paula (2017)
Sarcocystis spp. are obligatory intracellular protozoan parasites which can infect humans and animals. Most of Sarcocystis species were identified based on the detection of muscle cysts in different intermediate hosts (IH). Regarding to natural infection in definitive host, there are few reports which have reached to determining species of Sarcocystis. The present work was aimed to studying the occurrence of Sarcocystis spp. (oocysts and sporocysts) in mucosal scrapings of small intestine and fecal samples of one the most abundant wild canids from South America, Lycalopex gymnocercus (Pampas fox), and to identify the Sarcocystis spp. using molecular tools. A total of 131 free-living L. gymnocercus were sampled in rural areas located in several departments from Buenos Aires province, Argentina. Fecal samples from all the animals and 33 small intestines were analyzed. Fecal and mucosal scrapings samples were analyzed by sugar flotation method and once oocysts or sporocysts were detected, sedimentation was performed and DNA extracted with a commercial kit. A PCR was conducted using primers targeting a fragment of the 18S rRNA gene and the amplicons were purified and sequenced. Of the total Pampas foxes analyzed, 23 (17.6%) had Sarcocystis spp. oocysts/sporocysts in fecal and/or mucosal samples. Sarcocystis spp. sporocysts were detected in 13.0% (17/131) of fecal samples and in 39.4% (13/33) of mucosal samples by the initial sugar flotation. Twenty one L. gymnocercus samples were processed by DNA extraction and PCR. Molecular identification of Sarcocystis spp. infection was successfully achieved in 14 foxes and was distributed as follows: 4.6% S. cruzi (6/131), 3.8% Sarcocystis spp. using birds as IH (S. albifronsi and S. anasi among others, 5/131), 0.8% S. tenella (1/131) and 1.5% (2/131) with low homology (97%) with S. miescheriana. In one fecal sample with spherical oocysts, the sequencing results showed a 100% sequence identity with Hammondia heydorni. The results show that the mucosal scrapings are the eligible sample to identify prevalence and to proceed with species identification. Lycalopex gymnocercus is suggested as definitive host for S. cruzi, S. tenella and probably various Sarcocystis spp. using birds as intermediate hosts as well as for H. heydorni.